CONJUGATE OF A COMPLEX NUMBER

The conjugate of the complex number x + iy is defined as the complex number x - iy.

If z represents a complex number, then the complex conjugate of z is denoted by To get the conjugate of the complex number z, simply change the sign of i in z. For instance, 2 - 3i is the conjugate of 2 + 3i.

The product of a complex number with its conjugate is a real number. For instance,

(i) (a + ib)(a - ib) :

= a2 - (ib)2

= a2 - i2b2

= a2 - (-1)b2

= a2 + b2

(i) (3 + 4i)(3 - 4i) :

= 32 - (4i)2

= 9 - 42i2

= 9 - 4(-1)

= 9 + 4

= 13

Geometrically, the conjugate of of the complex number z is obtained by reflecting z on the real axis.

Geometrical Representation of Conjugate of a Complex Number

conjugateofcomplexnumber1.png
conjugateofcomplexnumber2.png

Note :

Two complex numbers x + iy and x - iy are conjugates to each other. The conjugate is useful in division of complex numbers. The complex number can be replaced with a real number in the denominator by multiplying the numerator and denominator by the conjugate of the denominator. This process is similar to rationalising the denominator to remove surds.

conjugateofcomplexnumber3.png

Solve Problems

Problem 1 :

Write the complex number given below in x + iy form, hence find its real and imaginary parts.

Solution :

To express the given complex number in the rectangular form x + iymultiply the numerator and denominator by the conjugate of the denominator to eliminate i in the denominator.

The complex number above is in the form x + iy.

Problem 2 :

Simplify the following expression into rectangular form.

Solution :

We consider

and

Therefore,

Problem 3 :

In the expression given below, find the complex number z in the rectangular form.

Solution :

2(z + 3) = (z - 5i)(1 + 4i)

2z + 6 = z + 4zi - 5i - 20i2

2z + 6 = z + 4zi - 5i - 20(-1)

2z + 6 = z + 4zi - 5i + 20

2z - z - 4zi = -5i + 20 - 6

z - 4zi = -5i + 14

z(1 - 4i) = 14 - 5i

Problem 4 :

Solution :

Problem 5 :

Find z-1, if z = (2 + 3i)(1 - i).

Solution :

z = (2 + 3i)(1 - i)

= 2 - 2i + 3i - 3i2

= 2 + i - 3(-1)

= 2 + i + 3

= 5 + i

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. SAT Math Videos

    May 22, 24 06:32 AM

    sattriangle1.png
    SAT Math Videos (Part 1 - No Calculator)

    Read More

  2. Simplifying Algebraic Expressions with Fractional Coefficients

    May 17, 24 08:12 AM

    Simplifying Algebraic Expressions with Fractional Coefficients

    Read More

  3. The Mean Value Theorem Worksheet

    May 14, 24 08:53 AM

    tutoring.png
    The Mean Value Theorem Worksheet

    Read More